Políticas públicas direcionadas a coleta seletiva no município de Sorocaba - SP - Spinosa, Clélia Maria do Carmo (2012)
The current society has reached a level of development where there is no return. Not live without the comforts available in modern life. What has become a serious problem was the lack of concern about the waste they generate. This work aims to study the practice of selective collection, which for a long time is made by civil society initiatives, in a greater or lesser degree of consciousness, providing your collaboration environment. Discusses the work of the collector who over the years has exercised his activity so unnoticed and under conditions often unworthy. The current society has reached a level of development where there is no return. Not live without the comforts available in modern life. What has become a serious problem was the lack of concern about the waste they generate. This work aims to study the practice of selective collection, which for a long time is made by civil society initiatives, in a greater or lesser degree of consciousness, providing your collaboration environment. Discusses the work of the collector who over the years has exercised his activity so unnoticed and under conditions often unworthy. Points as one possible solution the partnership between public authorities, cooperatives and companies that invest in social, providing the inclusion of scavengers. In this context, recalls the figure of the collector as an essential actor in this process, allowing selective and careful with the solid waste. Complemented the study it was found, by means of questionnaires, the improvements that have occurred in the context of cooperative work through socioeconomic collectors of recyclable material, in the municipality of Sorocaba-SP. scavengers organized in cooperatives recovered the self-esteem acquired consciousness criticizes and constantly seek new achievements. Points as one possible solution the partnership between public authorities, cooperatives and companies that invest in social, providing the inclusion of scavengers. In this context, recalls the figure of the collector as an essential actor in this process, allowing selective and careful with the solid waste. Complemented the study it was found, by means of questionnaires, the improvements that have occurred in the context of cooperative work through socioeconomic collectors of recyclable material, in the municipality of Sorocaba-SP. scavengers organized in cooperatives recovered the self-esteem acquired consciousness criticizes and constantly seek new achievements.